Generation Z and Travel Motivations: The Impact of Age, Gender, and Residence - Jorge Marques; Sofia Gomes; Mónica Ferreira; Marina Rebuá; Hugo Marques (Tourism and Hospitality)
This study investigates the relationship between demographic factors and travel motivations among Generation Z leisure tourists through the lens of the Travel Career Pattern (TCP) theory. More specifically, the research focuses on how gender, age, and area of residence influence the travel motivations of Generation Z. Using a quantitative approach, data were collected from 303 respondents aged 18 to 28 through an online survey. The questionnaire assessed 14 motivational factors and analyzed them in relation to the participants’ demographic characteristics using linear regression models. Results indicate that gender and age significantly influence travel motivations, with women showing higher interest in personal development and social relationships, while men prioritize nature and adventure. Furthermore, rural residents exhibit greater motivation for autonomy, self-development and self-realization, while urban residents lean towards novelty and social interactions. The findings offer valuable insights for tourism marketers, emphasizing the importance of creating segmented marketing campaigns based on demographic factors. It also contributed to overcoming the lack of studies that specifically cover this interrelation between the motivational factors of Generation Z and the demographic factors of age, gender and area of residence. Nevertheless, this study also has limitations, such as the use of a non-representative sample and the focus on quantitative methods, suggesting that future research should adopt qualitative approaches and examine additional demographic variables to gain deeper insights into youth travel motivations.